GEOCHEMISTRY OF OPHIOLITIC BASALTS FROM THE METCHOSIN IGNEOUS COMPLEX ON SOUTHERN VANCOUVER ISLAND, AND THEIR INFERRED PALEOTECTONIC SETTING - Constantin, Marc (Ofioliti, 2001)
Major and trace elements geochemistry of Early Eocene rocks from the Metchosin Igneous Complex, a partial ophiolite located on Vancouver Island provide insight on its paleotectonic origin. Major and trace elements composition of volcanic rocks from the Metchosin Igneous complex indicate that they have compositions akin to MORB. These volcanic rocks extend from N-MORB to E-MORB compositions in various trace elements tectonic discriminant diagrams, and therefore support the hypothesis that the Southern Vancouver Ophiolite formed in a transitional tectonic setting, likely a divergent plate margin located near a continent. Mantle normalized trace element patterns of basalts from the Metchosin Igneous Complex are similar to those of the Gulf of California. A plausible modern analogue is therefore the Gulf of California of the Red Sea where a mid-ocean ridge developed into a continental rift.